Anatomical changes of Ipomoea reptans due to mercury uptake and accumulation in contaminant soil - NITA TAUHIDA; ESSY HARNELLY; MUHAMMAD NASIR; MUHAMMAD BAHI (Jurnal Natural, 2022)
Heavy metal contaminants like mercury is a serious problem to human, animals, and some plants’ health. Phytoremediation is an alternative technique, which can remediate the contaminants from soil using a hyperaccumulator plant. The goal of this research was to study anatomical changes of plant main organs (roots, stems, and leaves) of  Ipomoea reptans which are assumed as a hyperaccumulator plant that grows in mercury contaminant. The mercury concentration of the growth medium was 0, 61.871, 92.258, and 107.046 ppb. Ipomoea reptans were harvested after 27 days. The anatomical changes of the plant’s main organs were observed by preparing the cross-section of roots, stems, and leaves of I. reptans. The result showed that mercury treatment has caused anatomical damage at the xylem vessel of the root, and decreased bulliform cell size. The anatomical damage was found only in the root of I. reptans. The mercury concentration in media decrease to 0 ppb (P0), 50,420 ppb (P1), 58,583 (P2), and 96,120 (P3).